Combination with Stereotactic Body Radiotherapy Offers a Promising Strategy to Overcome Resistance to Immunotherapy in Advanced Renal Cell Cancer. (28th November 2019) - Sun, Xiaowen; Gan, Lu; Na, Aru; Ge, Lingling; Chen, Baoqing; Liu, Jiaming
Abstract : Immunotherapy for renal cell cancer (RCC) has witnessed several developments for more than two decades. Checkpoint inhibitors, including anti-CTLA-4 and anti-PD-1/PD-L1 blockers, have changed the treatment landscape for patients with advanced RCC in the past 3 years. Despite these advances, more than 55% RCC patients become resistant to different immunotherapies without other treatment combination. Among various attempts at overcoming resistance to immunotherapy, stereotactic body radiotherapy (SBRT) has been found to potentiate the activity of immunotherapy agents through several potential mechanisms, including normalization of microvessels to alleviate tumor hypoxia, improvement in efficient delivery of drugs, abundant neoantigen exposure, and recruitment of antitumor immune cells to alter the immunosuppressive tumor microenvironment. Preclinical studies and clinical case reports have predicted that the combination of SBRT, an immunotherapy, may lead to remarkable results. This review aims to provide the biological basis for the feasibility of combining SBRT to overcome immunotherapy resistance and to review the currently available clinical evidence of this combination therapy in patients with advanced RCC.